Prototipe Sistem Manajemen Billing Dan Lampu Billiard Otomatis Berbasis IoT Dengan ESP32 Dan MQTT - Muhammad Jhonsen Syaftriandi; Rendy Almaheri Adhi Pratama; Yarza Aprizal; Feri Irawan (BULLET : Jurnal Multidisiplin Ilmu, 2025)
This prototype of an IoT-based Automatic Billiard Billing and Light Management System is designed to revolutionize billiard business operations, delivering significant efficiency and accuracy. The system integrates a powerful ESP32 microcontroller with the reliable MQTT protocol, creating a seamless communication network that enables remote monitoring and control. Sophisticated sensors installed on each billiard table are responsible for detecting the real-time duration of table usage, then transmitting this data to the server via ESP32 and MQTT. The collected data is then processed and presented in an intuitive and easily accessible application for business managers. This application not only displays the current status of each table and playtime duration information, but also automatically calculates rental fees based on predetermined rates. Furthermore, the system also has the capability to automatically control the billiard table lights, so that the lights only turn on when the table is in use, and turn off when not in use. Thus, this prototype system not only minimizes the potential for billing calculation errors and reduces the need for manual intervention, but also provides invaluable convenience in monitoring overall business activity, transparent billing management, and ultimately, increases the profitability of the billiard business.